Teams-Games-Tournaments on Student Activity and Achievement: Elaboration of the Cooperative Learning Model - Daryani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The purpose of this study was to determine the improvement of English students' activities and learning outcomes. This type of research is classroom action research. The study used grade VII students from Al Firdaus Gubug's middle school IT program as the sample. The study employed both test and non-test data collection techniques. Data analysis techniques use quantitative descriptions. The study's results demonstrated an increase in student learning outcomes, both before and after learning improvements, from cycle I to cycle II. Before learning improvements, 31.82% of students completed their learning outcomes, 63.64% in cycle I, and 100% in cycle II. The activity failed to meet 68.18% of the student learning outcomes, 36.36% of cycle I, and 0% of cycle II before the improvements were made. The analysis and findings suggest that implementing the TGT (Teams Games Tournaments) cooperative learning model in English, specifically for identifying elements in children's stories, can enhance student learning outcomes.